Water quality assessment of groundwater resources in rural areas of Karachi, Pakistan - Suresh Kumar Panjwani; Muhammad Yar Khuhawar; Ghulam Murtaza; Vinod Kumar; Zohaib ur Rehman Bughio; Paryanka Devi; Indra Devi Sewani (International Journal of Advances in Applied Sciences, 2024)
The quality of drinking water directly controls many diseases and affects the growth of the human body. The provision of quality water is a major concern around the world, especially for developing countries that have poor environmental rules, insufficient water supply, and poor drainage systems. Considering these issues, this research was undertaken to assess drinking water quality in the rural areas surrounding Karachi, Pakistan. Samples were collected in the monitoring of the Pakistan Council of Research in Water Resources (PCRWR) and tested for physicochemical and bacteriological parameters (PCB) using geographical information system (GIS). Further, the results were compared with World Health Organization (WHO) standards for human consumption. An analysis of 35 drinking water samples revealed that 14% exceeded the permissible ranges for physical parameters. Moreover, 60% of the samples were deemed unsafe for consumption as the levels of inorganic substances surpassed permissible ranges outlined by WHO. All water samples contained coliform bacteria, making them unsafe, and 46% were contaminated with E. coli, highlighting the urgent need for improved sanitation and water treatment infrastructure in the area.